The role of forest in supplying soil nutrients in agricultural production system in the mid hills of Nepal - Oli, Krishna P.; Manandher, Mangal S. (Banko Janakari, 2017)
Abstract available on the PDF Banko Janakari Vol.12(1) 2002: 27-34